2021
DOI: 10.3390/ph14050431
|View full text |Cite
|
Sign up to set email alerts
|

EEG and Sleep Effects of Tramadol Suggest Potential Antidepressant Effects with Different Mechanisms of Action

Abstract: Tramadol is a widely used, centrally acting, opioid analgesic compound, with additional inhibitory effects on the synaptic reuptake of serotonin and noradrenaline, as well as on the 5-HT2 and NMDA receptors. Preclinical and clinical evidence also suggests its therapeutic potential in the treatment of depression and anxiety. The effects of most widely used antidepressants on sleep and quantitative electroencephalogram (qEEG) are well characterized; however, such studies of tramadol are scarce. Our aim was to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The sleep-wake stages were classified using SleepSign for Animal sleep analysis software (Kissei Comtec America Inc., Fort Lee, NJ, USA), using conventional criteria ( Kantor et al, 2004 ; Koncz et al, 2021 ). We used the automatic scoring feature of the software to score the vigilance stages at first; after that, visual supervision was conducted by researchers who were unaware of the treatment of the rats.…”
Section: Methodsmentioning
confidence: 99%
“…The sleep-wake stages were classified using SleepSign for Animal sleep analysis software (Kissei Comtec America Inc., Fort Lee, NJ, USA), using conventional criteria ( Kantor et al, 2004 ; Koncz et al, 2021 ). We used the automatic scoring feature of the software to score the vigilance stages at first; after that, visual supervision was conducted by researchers who were unaware of the treatment of the rats.…”
Section: Methodsmentioning
confidence: 99%
“…44 Recent animal studies have also found that tramadol dose-dependently reduces sleep time during rapid eye movement sleep and increases the attack latency of rapid eye movement sleep. 45 In this study, we found that compared with the control group, tramadol can directly improve the sleep score of patients on the first to third day after surgery. One study has indicated that opioids can affect the quality of sleep, and both acute (for sedation or postoperative analgesia) or chronic (long-term for chronic pain) can disrupt sleep patterns.…”
mentioning
confidence: 68%
“…Rats (9 weeks old), weighing between 290–325 g at surgery, were implanted with EEG and electromyographic (EMG) electrodes under 2% isoflurane anesthesia, using a Kopf stereotaxic instrument, as described earlier [ 6 , 27 , 28 , 29 ]. Briefly, for frontoparietal EEG recordings, stainless steel screw electrodes were placed epidurally over the left frontal cortex (1.5 mm lateral and 2.0 mm anterior to bregma) and over the left parietal cortex (1.5 mm lateral and 2.0 mm anterior to lambda), and a ground electrode was equipped over the cerebellum.…”
Section: Methodsmentioning
confidence: 99%